Intercomparison of Solid Precipitation Derived from the Weighting Rain Gauge and Optical Instruments in the Interior Qinghai-Tibetan Plateau. (27th July 2015) - Zhang, Lele; Zhao, Lin; Xie, Changwei; Liu, Guangyue; Gao, Liming; Xiao, Yao; Shi, Jianzong; Qiao, Yongping
Abstract : Due to the light precipitation and strong wind in the cold season, it is hard to get credible solid precipitation on the Qinghai-Tibetan plateau (QTP). To address this issue, two kinds of optical instruments, the Thies Laser Precipitation Monitor (LPM) and OTT laser-optical Particle Size Velocity (Parsivel), were used on QTP. The measured precipitation was compared with the precipitation derived from Geonor T-200B precipitation gauge (Geonor). The results showed that Geonor was hard to catch light precipitation (precipitation amount was less than 1 mm during a single event) when the wind speeds were higher than 3.5 m/s. Even when the wind speeds were smaller than 3.5 m/s, about 44% of such light precipitation events were not recorded by Geonor. The optical instruments had much better performance in recording light precipitation. Three methods were used to correct Geonor measurements of daily solid precipitation and the corrected values were set as reference for assessing the performance of LPM and Parsivel; the results showed that LPM had good performance in measuring the solid precipitation but Parsivel overestimated the precipitation amount. Methods for correcting Geonor's hourly solid precipitation and recalculating Parsivel's solid precipitation amount were also proposed in this paper.